2005
DOI: 10.1506/5fq9-anea-t8j0-u6gy
|View full text |Cite
|
Sign up to set email alerts
|

Independence Threats, Litigation Risk, and the Auditor's Decision Process*

Abstract: This study examines the effect of independence threats and litigation risk on auditors' evaluation of information and subsequent reporting choices. Using a Web‐based experiment, I tracked auditors' information gathering and evaluation leading to a going‐concern reporting decision. Specifically, 48 audit managers assessed client survival likelihood, gathered additional information, and suggested audit report choices. I found that auditors facing high independence threats (fear of losing the client) evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(93 citation statements)
references
References 47 publications
5
83
0
4
Order By: Relevance
“…Numerous other studies provide additional evidence that auditors' incentives affect judgments about appropriate accounting treatment and/or appropriate audit opinion. Particular incentives examined include need to maintain office profitability (e.g., Trompeter 1994), client fee pressure (e.g., Gramling 1999; Houston 1999), client preference (Haynes et al 1998), fear of client loss (Farmer et al 1987;Blay 2005), and potential litigation exposure (e.g., Farmer et al 1987;Hackenbrack and Nelson 1996;Braun 2001;Blay 2005).…”
Section: Incentives (Link 5)mentioning
confidence: 99%
“…Numerous other studies provide additional evidence that auditors' incentives affect judgments about appropriate accounting treatment and/or appropriate audit opinion. Particular incentives examined include need to maintain office profitability (e.g., Trompeter 1994), client fee pressure (e.g., Gramling 1999; Houston 1999), client preference (Haynes et al 1998), fear of client loss (Farmer et al 1987;Blay 2005), and potential litigation exposure (e.g., Farmer et al 1987;Hackenbrack and Nelson 1996;Braun 2001;Blay 2005).…”
Section: Incentives (Link 5)mentioning
confidence: 99%
“…If the client constitutes a relatively large part of an auditor's portfolio, an auditor has an incentive to retain the client to warrant a future source of revenues and profits and therefore, to compromise independence and act in favor of the client (Blay, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Auditors tend to be more responsive to the risk of litigation when it conflicts with incentives to seek profits (Tucker et al, 2003;Blay, 2005) 9 and previous researchers have reported that auditors should consider the risk of litigation in their opinion decisions (Blay, 2005;Cahan and Zhang, 2006;Elder et al, 2009). A number of 7 For more laws and regulations on the Matters Required to be Included in the Corporate Bylaws of Credit Rating Agencies, see the web site http://law.fsc.gov.tw.…”
Section: Auditormentioning
confidence: 99%